Peningkatan Potensi Biji Kelor (Moringa oleifera) sebagai Pangan Pencegah Hiperkolesterolemia - Annisa Nazifa Salman; Endang Prangdimurti; Dase Hunaefi (Jurnal Ilmu Pertanian Indonesia, 2023)
Moringa (Moringa oleifera) seeds contain good nutritional constituents and several components that can potentially reduce cholesterol levels, namely oleic acid, phytosterols, and dietary fiber. However, it tastes bitter, so it needs to be treated so that the bitter taste disappears but does not affect much of the content that can lower cholesterol. This study aims to get moringa seeds that are not bitter and have the potential to prevent hypercholesterolemia. The soaking treatment of peeled moringa seeds in either water or 3.5% NaCl salt, followed by 80 minutes of boiling, resulted in moringa flour with a very low bitter taste. The oleic acid content of the seed flour from soaking treatment with water or salt by boiling for 40 or 80 minutes is still high, in the range of 69–72%. Oleic acid is known to improve blood cholesterol profiles. The content of phytosterols, one of the cholesterol absorption inhibitors, from moringa flour treatment of 27–29 mg/100 g dw, is much higher than control flour (15 mg/100 g dw). The dietary fiber content of moringa seeds (total dietary fiber, soluble dietary fiber, insoluble dietary fiber) generally does not change after treatment. The results showed that soaking moringa seeds in water for 24 hours, followed by boiling for 80 minutes, produced moringa flour that can be used to develop hypercholesterolemia prevention foods. Keywords: bitter taste, cholesterol, moringa seeds, oleic, phytosterol